MANAJEMEN WAKAF PONDOK MODERN DARUSSALAM GONTOR: ANALISIS MODEL PEMELIHARAAN, PENGEMBANGAN WAKAF DAN KESEJATERAAN UMAT - Jarman Arroisi; Syamsuri Syamsuri (Ijtihad, 2020)
Waqf Management Gontor is a management relies on the spirit of carrying out the value of the five souls, five terms, philosophy, sunnah and discipline. With high commitment from YPPWPM officials and Gontor families, Gontor was finally able to maintain, develop waqf and prosper the ummah. However, that does not mean that Gontor waqf management is final and barrier-free. Not a few problems that confront, even physical war has occurred to maintain waqf from the control of irresponsible people. This paper examines the management model of YPPWPM in maintaining and expanding waqf. In addition, this study also intends to observe the pattern of waqf expansion carried out to bring prosperity. With the descriptive method, this study gets three important conclusions. First, Commitment, work ethic, excellent discipline and togetherness from YPPWPM officialsto manage and all the big family of Gontor in implementing the values of the five souls and the five levels are the key to the success of Gontor waqf. Second, the maintenance pattern of Gontor waqf begins with the struggle to obtain a Decree on the appointment of Gontor YPPWPM as a Legal Entity that can have ownership rights on land. The struggle was continued with various efforts to expand waqf since fundraising from benefactors to buy livestock, to develop in the agricultural, plantation, convection, agriculture, transportation services and so on sectors. Third, the maintenance and development efforts of the waqf do not only add to the quantity of waqf but are also able to prosper the employees, teachers and all cadres.